Dinamika Bullying di Lingkungan Pesantren Perspektif Psikososial dan Pendidikan Islam yang Holistik - Ridwan Hermawan; Istikhori Istikhori; Cacang Cacang; E.Komarudin; Hasbullah Karim Alfauzi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The phenomenon of bullying that occurs in the pesantren environment is not only a social problem, but also reflects a crisis in the internalization of Islamic educational values. This study aims to examine the dynamics of bullying in Islamic boarding schools from a psychosocial perspective and Islamic educational values. With a literature study approach and qualitative content analysis, this study explores various theories, empirical findings, and expert views obtained from relevant journals, books, and scientific works. The results of the study show that the practice of bullying in pesantren often stems from power relations that are institutionalized through the hierarchy structure of seniority, as well as weak supervision of the process of internalizing Islamic values among students. The values of Islamic ukhuwah, justice, and compassion that should be the spirit of Islamic education are often eroded by a culture of silence, neglect, or even the wrong perception that bullying is part of discipline. In fact, the concept of Islamic education not only emphasizes the mastery of the knowledge of tools (tsaqafah), but also the formation of intellect ('aqliyah), soul (nafsiyah), and Islamic personality (syakhsiyah Islamiyah) based on a strong aqidah. Bullying prevention requires deeper Islamic character education, strengthening social control, and psychosocial approaches to maintain mental and spiritual balance of students. The implications of this study emphasize the importance of a holistic and civilized pesantren management strategy, by fostering an anti-bullying culture, creating a safe, harmonious, and harmonious learning environment that is in line with the main goals of Islamic education. Thus, pesantren are expected to be able to form students who are not only intellectually intelligent, but also have noble morals, high social spirit, empathy, and have a strong Islamic personality and full of integrity.